Development Of A Strategy For Writing Scientific Research Based On The Theory Of Social Constructivism According To Lev Semyonovich Vygotsky - Mishbahuddin, Mohamad (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
Scientific writing is an essential skill in the academic world, especially in higher education, where scientific writing ability is an important indicator in assessing the academic quality of students. In the Arabic Language Education Study Program of STAI Al-Yasini Pasuruan, even though students are in their final semester, many of them still face obstacles in compiling scientific works that meet academic standards. This study aims to analyze the factors that affect the scientific writing skills of students in the 6th semester of the Arabic Language Education Study Program STAI Al-Yasini Pasuruan, with a quantitative approach. The focus of this research is to identify the influence of scientific writing training, the use of technology, and students' understanding of scientific writing rules on the quality of the scientific manuscripts produced. The research method used is a quantitative method with a correlational design. Data was collected through the distribution of a questionnaire consisting of 30 question items that measured three main variables: scientific writing training, the use of technology in scientific writing, and understanding of the rules of scientific writing. This questionnaire was distributed to 100 6th semester students as a research sample. The collected data was then analyzed using descriptive statistics to describe the profile of students' scientific writing skills, as well as multiple linear regression analysis to test the influence of each variable on the quality of scientific writing. The results of the study show that the scientific writing training received by students has a significant influence on their skills in compiling scientific writings that are systematic and in accordance with academic rules. The use of technology, such as reference management apps (Mendeley, Zotero) and anti-plagiarism tools, has also been proven to help students improve the quality of their writing. In addition, students' understanding of the basic principles of scientific writing, such as organizing ideas, using correct citations and references, and appropriate writing formats, plays an important role in influencing the quality of the scientific manuscripts produced. This study provides recommendations to improve the scientific writing training program on campus by strengthening a technology-based approach and deepening students' understanding of the applicable scientific writing rules. The findings of this study are expected to contribute to the development of higher education curriculum, especially in supporting the improvement of students' scientific writing skills, as well as providing a basis for more effective learning policies in the Arabic Language Education Study Program.